NEW DATA ON PALEOGENE BIOSTRATIGRAPHY OF THE EASTERN CRIMEA - Bugrova E.M.; Zakrevskaya E.Yu.; Tabachnikova I.P. (My University, 2002)
New data on different organic remains and biostratigraphy of the Paleocene-lowermost Eocene type section in the Indol structural-facies zone of the Indol-Kuban' depression of the Eastern Crimea are discussed. The section demonstrates a succession of different faunal types from the shallow-water accumulation zone of carbonates (the southwestern Crimea) to relatively deep-water zone of pelagic sedimentation (the northern Caucasus). According to distribution of planktonic foraminifers, the section is subdivided into Acarinina acarinata, Morozovella subbotinae (s.1.), Morozovella aragonensis, and Acarinina bullbrooki zones, the standard units of the Paleogene scale elaborated for southern regions of the former USSR. Discocyclins discovered from the Paleocene interval of the section characterize the SBZ3, SBZ10, and SBZ11 zones of the Tethyan zonation of larger foraminifers. Nannoplankton assemblages studied for the first time in this section correspond, entirely or partly, to those of Heliolithus kleinpelli (NP6), Heliolithus riedeli (NP8), Discoaster multiradiatus (NP9), Discoaster lodoensis (NP13) and Discoaster sublodoensis (NP14) zones. Smaller foraminifers allowed subdivision of the section into new Anomalina danica, Karreriella zolkaensis, Asterigerina bartoniana kaasschieteri, and Pseudogaudryina pseudonavarroana (with two subzones) local zones correlated with regional zones of this faunal group. Transformations of the basin ecosystem and correlation with sections of neighboring regions are briefly discussed.
Keywords: Paleogene; Cenozoic::Paleogene; Кайнозой::Палеоген